Imaging of a rare case of an ovarian collision tumor between a giant cystadenoma and a fibroma in a postmenopausal woman - Masino, Federica; Gifuni, Rossella; Dayala Sundaram , Antony Samy; Rajaram, Akash; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2024)
Ovarian collision tumors are rare and poorly documented in the scientific literature. Usually, the diagnosis is based on post-operative histopathological examination; hence the pre-operative radiological appearance is rarely documented. We report the first case of an ovarian collision tumor, well documented radiologically and histologically diagnosed after bilateral ovariectomy in a postmenopausal woman. Abdomen X-rays, a pelvic and transvaginal ultrasound, and a contrast abdomen CT were performed. Histological results diagnosed a bilateral cystadenoma, with the coexistence of fibroma on the left ovary. On the left side, the cystadenoma was giant.